Pemenuhan Hak Istri oleh Suami Pecandu Game Online: Studi Normatif-Empiris Menurut KHI di Tanjungbalai: Wife’s Rights Fulfillment by Husbands Addicted to Online Games: Normative-Empirical Study in Tanjungbalai - Adha, Ismail; Mukhshin, Abdul (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study examines the fulfillment of wives’ rights by husbands addicted to online gaming from a normative-empirical perspective according to the Compilation of Islamic Law (KHI) in Tanjungbalai City, Indonesia. The phenomenon of online gaming addiction among husbands has created new challenges for the resilience of Muslim families, especially regarding the fulfillment of wives’ rights in economic, emotional, and spiritual aspects. Employing a qualitative approach, this research used in-depth interviews with husbands, wives, and religious figures in two districts. The findings reveal that online gaming addiction contributes to the neglect of family support, deterioration of communication and attention from husbands, and increased psychological stress and household conflict. Furthermore, wives often face obstacles in accessing legal and social protection due to strong patriarchal culture and limited digital literacy. Although KHI stipulates a fair distribution of rights and obligations between husband and wife, its implementation at the local level faces significant structural and cultural challenges. These results highlight the urgency of strengthening digital literacy, family law education, and collaboration among religious institutions, communities, and government to build a responsive family protection system in the digital era. This study contributes to the development of contemporary Islamic family law discourse and the protection of women's rights in the dynamics of digital society.